6x + 4y = 18 ---(1)

x - y = 4/3 ---(2)

Multiply equation (2) by 6

6x - 6y = (4/3)*6

6x - 6y = 8 ---(3)

Subtract equation (3) from equation (1)

6x + 4y - (6x - 6y) = 18 - 8

6x + 4y - 6x + 6y = 10

10y = 10

y = 10/10

y = 1

Substitute the value of y in equation (1)

6x + 4*1 = 18

6x + 4 = 18

6x = 18 - 4

6x = 14

x = 14/6

x = 2.3

ANSWER: A) Solution of the system is x = 2.3 and y = 1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up